Association of bacteria in pancreatic fistula fluid with complications after pancreatic surgery. Issue 3 (16th April 2020) - Demir, E; Abdelhai, K; Demir, I E; Jäger, C; Scheufele, F; Schorn, S; Rothe, K; Friess, H; Ceyhan, G O
Abstract: Background: Pancreatic fistula (PF) is a common complication after pancreatic surgery. It is unclear how microbes in PF fluid affect outcomes and which microbes are present after pancreatoduodenectomy (PD) and distal pancreatectomy (DP). The aim of this study was to compare the microbiological spectrum of PF fluid after PD versus DP, and its association with postoperative complications. Methods: Bacterial strains and antibiotic resistance rates of bacterial swabs obtained from the PF fluid of patients who underwent DP or PD were analysed. Cultured bacteria were classified as Enterobacterales and as 'other intestinal and non-intestinal microorganisms' based on whether they are typically part of the normal human intestinal flora. Results: A total of 847 patients had a pancreatic resection (PD 600; DP 247) between July 2007 and December 2016. Clinically relevant PF was detected in 131 patients (15·5 per cent). Bacterial swabs were obtained from 108 patients (DP 47; PD 61), of which 19 (17·6 per cent) were sterile. Enterobacterales were detected in 74 per cent of PF fluid swabs after PD, and in 34 per cent after DP. Infected, polymicrobial or multidrug-resistant PF fluid was more common after PD (rates of 95, 50 and 48 per cent respectively) than after DP (66, 26 and 6 per cent respectively). Patients with higher grade complications (Clavien–Dindo grade IV–V) or grade C PF had more Enterobacterales and multidrug-resistant Enterobacterales in the PF fluid after DP. Conclusion: Enterobacterales and multidrug-resistant bacteria are detected frequently after PD and DP, and are associated with more severe complications and PF in patients undergoing DP. Graphical Abstract: This study showed that, despite the absence of intestinal lumen opening, pancreatic fistulas after distal pancreatectomy frequently contain intestinal bacteria, which markedly worsen the clinical outcome. Understanding the pathogenetic mechanism behind this high prevalence of intestinal bacteria within distal pancreatectomy-associated pancreatic fistulas may help to generate effective therapeutic regimens. Enterobacteria associated with complications after distal pancreatectomy